Stakeholder collaboration to support accountability in village fund management and rural development - Fannidya Hamdani Zeho; Ardian Prabowo; Roro Ayu Estiningtyas; Mahadiansar Mahadiansar; I Gede Eko Putra Sri Sentanu (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2020)
The village government has an substantial responsibility in managing human resources to produce regional economic benefits. This research aims to identify the stakeholder collaboration to support accountability in village fund management and rural development.  This study used an interactive approach with data collection methods such as structured interviews, documentation, and observation. The object of the study is village officials in Pranggang Village, Plosoklaten District, Kediri Regency, East Java Province. The results of the study showed that the village government has not optimally carried out its role in involving more stakeholders.  Collaborative stakeholders in managing village funds involved village government officials, activity management team and community.   They play a positive role in bringing about village accountability in managing village funds. An increased community participation contribute to program evaluation activities and effectiveness in the village financial management. The accountability of the village funds utilization has met the Home Affairs Ministerial Regulation number 113 of 2014. In addition, social accountability has been applied in various forms of effective interactions between the community and village government. Much efforts are required to improve the quality of human resources through more stakeholder engagement, training activity and  community empowerment.   JEL Classification: H72; H83; O20